Penerapan Guided Inquiry Learning untuk Meningkatkan Keterampilan Interpretasi Data Siswa Kelas XI IPA 4 Tahun Pelajaran 2016/2017 pada Materi Sistem Ekskresi Manusia - Ramadhani Latifah Faeka Murni; Harlita Harlita; Sri Widoretno (Universitas Sebelas Maret, 2017)
The objectives of this research is to improve the skills of students interpreting data of class XI IPA 4in teaching and learning process at biology subject with materials of human excretory system. The result of the observations for each skill’s indicator of data interpretation was less than < 30% showed a lack of the students’ data interpretation skill, so it is needed a learning model that accommodates interpreting data. The interpretation skill can be trained through experiment activity. One of the learning model that accommodates experiment is guided inquiry learning model. The method of data collection is through observation, interviews, and documentation. The research data was the students’ score that indicate the activity of data interpretationbased on Harlen. The results of the implementation of guided inquiry learning model inhuman exretory system material showed an increase of students’activity in interpreting data for each indicator. The average score of interpreting data at the first cycle reaches more than 50% and improve at second cycle more than 75%. Based on the result of the research, can be concluded that the implementation of guided inquiry learning model inhuman exretory system material is able to improve students’ interpretation data skill, although the improvement were varied in each interpretation data indicators.